Trends in Immunization Completion and Disparities in the Context of Health Reforms: The case study of Tanzania - Semali Innocent A (BMC, 2010)
Abstract Background Of global concern is the decline in under five children mortality which has reversed in some countries in sub Saharan Africa (SSA) since the early 1990 s which could be due to disparities in access to preventive services including immunization. This paper is aimed at determining the trend in disparities in completion of immunization using Tanzania Demographic and Health Surveys (DHS). Methods DHS studies randomly selected representative households from all regions in Tanzania since 1980 s, is repeated every five years in the same enumeration areas. The last three data sets (1990, 1996 and 2004) were downloaded and analyzed using STATA 9.0. The analysis included all children of between 12-23 months who would have completed all vaccinations required at 12 months. Results Across the time periods 1990, 1996 to 2004/05 the percentage of children completing vaccination was similar (71.0% in 1990, 72.7% in 1996 and 72.3% in 2005). There was no disparity in completion of immunization with wealth strata in 1990 and 1996 (p > 0.05) but not 2004. In 2004/05 there was marked disparity as most poor experienced significant decline in immunization completion while the least poor had significant increase (p < 0.001). All three periods children from households whose head had low education were less likely to complete immunization (p < 0.01). Conclusion Equity that existed in 1990 and more pronounced in 1996 regressed to inequity in 2005, thus though at national level immunization coverage did not change, but at sub-group there was significant disparity associated with the changing contexts and reforms. To address sub-group disparities in immunization it is recommended to adopt strategies focused at governance and health system to reach all population groups and most poor.